Urgent and emergent repair of complex aortic aneurysms using an off-the-shelf branched device - Nana, Petroula; Spanos, Konstantinos; Jakimowicz, Tomasz; Torrealba, Jose I.; Jama, Katarzyna; Panuccio, Giuseppe; Rohlffs, Fiona; Kölbel, Tilo (Frontiers in Cardiovascular Medicine, 2023)
Introduction Endovascular repair using off-the-shelf endografts is a viable solution in patients with ruptured or symptomatic complex aortic aneurysms. This analysis aimed to present the peri-operative and follow-up outcomes in urgent and emergent cases managed with the t-Branch multibranched thoracoabdominal endograft. Methods Prospectively collected data from all consecutive urgent and emergent cases managed in two aortic centers between January 1st, 2014, to November 30th, 2022, using the t-Branch device (Cook Medical Inc., Bjaeverskov, Denmark) were analyzed. Patients presenting with ruptured aortic complex aneurysms were characterized as emergent and patients with aneurysms >90 mm of diameter, or symptomatic aneurysms were characterized as urgent. Technical success, 30-day mortality, major adverse events (MAE) and spinal cord ischemia (SCI) rates were assessed. Results 225 patients (36.5% females, 72.5 ± 2.8 years) were included; 73.0% were urgent. The mean aneurysm diameter was 109 ± 3.9 mm and 44.4% were type I–III TAAAs. Females (p = .03), para-renal aneurysms (p = .02) and ASA score IV (p < .001) were more common in emergent cases. Technical success was 97.8%. Thirty-day mortality and MAE rates were 17.8% and 30.6%, respectively. SCI rate was 14.7%, (4.8% paraplegia rate) with 22.2% of patients receiving prophylactic cerebrospinal drainage. Thirty-day mortality (13.3% vs. 26.7%, p = .04) and MAE (26.0% vs. 43.0%, p = .02) were more common among emergent cases while technical success (97.6% vs. 98.3%, p = .9), and SCI (13.3% vs. 18.3%, p = .4) were similar. Survival at 12-months was 83.5% (SE 5.9%) for the urgent and 77.1% (SE 8.2%) for the emergent group (log rank, p = 0.96). Conclusion T-Branch represents an effective and safe solution for the management of urgent and emergent cases with complex aortic aneurysms, with high technical success, promising early mortality and SCI rates.